Protective effect of ethanolic Feronia elephantum Correa fruit extract on high-fat diet induced steatohepatitis in rats - Diarti, Maruni Wiwin; Harmi, Khoviya Yuwina Selinada; Ahsani, Dwi Nur (Faculty of Medicine, Universitas Trisakti, 2021)
BACKGROUND A high-fat diet can lead to hyperlipidemia which will end up as liver damage (steatohepatitis). Ethanolic Feronia elephantum Correa fruit extract (EFEC) has an antioxidant activity which is expected to overcome hyperlipidemia in the liver. The objective of this study was to determine the effects of EFEC on liver function and morphological changes in rats.METHODSThis was an experimental study with a post-test only group design. A total of 20 male Wistar rats aged 2-4 months were randomized into 5 groups, A= negative control, B= positive control (high fat diet + 10 mg/kgBW simvastatin), C = high fat diet + 500 mg/kgBW EFEC fruit extract, D = high fat diet + 600 mg/kgBW EFEC, and E = high fat diet + 700 mg/kgBW EFEC). High-fat diet was given for 4 weeks (quail egg yolks, 10ml/200gBW). EFEC was administered for 4 weeks after induction of hypercholesterolemia. Examination of liver serum glutamic oxaloacetic transaminase (SGOT) and serum glutamic pyruvic transaminase (SGPT) was performed on rat blood serum and histopathological examination was carried out using steatohepatitis grading. One way ANOVA test and Post-Hoc Tamhane’s test were used to analyze the data. RESULTSAdministration of EFEC at 700 mg/kgBW improved the liver enzymes (p=0.00 for SGPT and SGOT) and steatohepatitis grading in high-fat diet induced rats (mild condition, E = 75% vs A = 100% mild)CONCLUSIONEthanolic Feronia elephantum Correa fruit extract at 700 mg/kgBW was able to improve steatohepatitis in high-fat diet induced rats.